2020
DOI: 10.1111/jpm.12672
|View full text |Cite
|
Sign up to set email alerts
|

Is the mental health of young students and their family members affected during the quarantine period? Evidence from the COVID‐19 pandemic in Albania

Abstract: Introduction The use of quarantine method has a significant impact on mental health status. Aim This study aimed to assess the levels of depression among bachelor and master university students (nurses/midwives) and their family members’ during the quarantine period of COVID‐19 pandemic. Method A cross‐sectional study was conducted in Vlora University, Albania. Patient Health Questionnaire (PHQ‐9) was used. Institutional e‐mails of all active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
3
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 32 publications
7
74
3
13
Order By: Relevance
“…In addition the data began to be collected minimally two weeks after the start of quarantine, so they also met the PHQ-9 criterion that assesses the mental state of participants in the past two weeks. The results are similar to a study carried out in Albania among family members of university students where 22.8% and 15.6% of them showed respectively mild and moderate deppression (Mechili et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…In addition the data began to be collected minimally two weeks after the start of quarantine, so they also met the PHQ-9 criterion that assesses the mental state of participants in the past two weeks. The results are similar to a study carried out in Albania among family members of university students where 22.8% and 15.6% of them showed respectively mild and moderate deppression (Mechili et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The finding that psycho-social threats during lockdown are a strong predictor for an impact on social-emotional problems of children and adolescents is quite consistent to prior findings and research based assumptions as mentioned in the introduction (Clemens et al, 2020;Fontanesi et al, 2020;Mechili et al, 2020;Spinelli et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…Despite acknowledging possible negative effects of school lockdown for mental health, Chawla et al (2021) also assumes that for SEN students this measure could mean an absence of bullying or school pressure and therefore in some ways might even have positive effects on psychological well-being. The assumption of the pandemic's negative impact on childrens' wellbeing can furthermore be theoretically underpinned by findings that parental stress during the lockdown may be transferred to their children and that the lockdown situation might lead to a higher load of in-family violance, emotional neglect, or isolation (Clemens et al, 2020;Fontanesi et al, 2020;Mechili et al, 2020;Spinelli et al, 2020). Furthermore, it can be shown that the pandemic situation challenges the system of public child welfare -and although the child welfare practitioners seem to adjust to the new situation, it cannot be said which long-term effects the lockdown may have on public child welfare systems (Baginsky & Manthorpe, 2020;Jentsch & Schnock, 2020).…”
Section: Impact Of Covid-19 Pandemic and School Lockdownmentioning
confidence: 99%
“…A large number of studies examined the impact of the lockdown on mental health (Branley-Bell and Talbot, 2020;Cellini et al, 2020;Mechili et al, 2020;Pieh et al, 2020;Verma and Mishra, 2020), as well as its relation with certain constructs such as anxiety and depression. Adams-Prassl et al (2020) reported negative quarantine effects on the mental health of the United States population while other researchers found that lockdown affects sleep quality (Huang and Zhao, 2020;Rossi et al, 2020) and that higher levels of anxiety can be explained by the time spent reading and discussing news about COVID-19 (Rosen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%